Survey and export lumber for potentially pathogenic nematodes, (Bursaphelenchus spp), in Russia - Kulinich, Oleg (2012)
The pinewood nematode (PWN) B. xylophilus occurs widely in North America and East Asia and is a quarantine pest for Europe. However, recently it was detected in Portugal (Mota et al., 1999) where it may have been introduced on wood imported from China or Russia. Russia exports over 40x106 m3 of wood products per year, most of which to Europe. Officially the PWN is absent in Russia but recently, Braasch et al. (2001) reported it in wood imported from Siberia. This resulted in our surveying in the forests and woodlands of Siberia to determine if the PWN occurs in this part of Russia and also to identify other nematode species that might pose a threat to Russian and European forests. Conifer samples were collected in 2002-2003 by the Russian Forest and Plant Quarantine Service or during our own surveys in some of these regions. In total, 631 samples were analyzed and no typical B. xylophilus (e.g. females possessing a round tail) was found in any of the samples. The closely related, but non-pathogenic B. mucronatus, was found in five of the nine sampled areas. Morphological identification was confirmed by PCR-RFLP studies and sequences of ITS-rDNA at the Agricultural Research Centre in Belgium (Kulinich et al. 2003). The highest occurrence of B. mucronatus was in samples from the Ural Mountains and the Irkutsk region (28.8 and 20.2% respectively). Special attention was directed to sampling in the Krasnoyarsk region from which Braasch et al. (2001) reported finding B. xylophilus in lumber imported into Germany. Some 368 samples was analyzed from this region with only four samples yielding B. mucronatus. To date, 10 species of Bursaphelenchus have been found in Russia. The goals of past and future work was/is to determine (i) if the PWN occurs in Russia, especially in the harsh-climate Krasnoyarsk region and (ii) also what other Bursaphelenchus species recorded in Russia may threaten Russian and European forests.